Juncture interview: Bonnie Honig. Issue 4 (7th March 2013) - Honig, Bonnie
Abstract : Political theorist, Bonnie Honig, talks to Juncture about some of the driving forces behind her work and importance of 'public things' in a vibrant democracy.